Dėl kelių Marijampolės apskrities vandenvardžių, papildžiusių ir patikslinusių esamus hidronimijos duomenis - Sviderskienė, Dalia (Baltistica, 2010)
ON SEVERAL HYDRONYMS OF MARIJAMPOLĖ COUNTY UPDATING CURRENT HYDRONYMY DATAUnique resources of toponyms accumulated during the interwar and afterwar period in Lithuania are stored at the Department of Onomastics in the Institute of the Lithuanian Language. Data from questionnaires of the interwar period, i.e. toponyms accumulated by former counties, are among the most scientifically valuable. The author of this article selected the place names of Marijampolė County recorded in the language spoken in thirteen rural districts. Authentic and previously unexamined material was divided according to the type of objects named: names of water bodies (hydronyms), names of inhabited locations and names of uninhabited locations (names of various other objects located on the surface of the earth). In the analysis and discussion of ways of place name formation and evaluation of the origin of toponyms within the indicated groups, the focus was on the authenticity of toponyms, especially hydronyms, recorded in the interwar period.To date there are two official published hydronym sources: Lietuvos TSR upių ir ežerų vardynas (Index of Names of Lakes and Rivers of the Lithuanian SSR) (editor E. Grinaveckienė, Vilnius: Valstybinė politinės ir mokslinės literatūros leidykla, 1963) and Lietuvių hidronimų etimologinis žodynas (Etymological Dictionary of Lithuanian Hydronyms) by A. Vanagas (Vilnius: Mokslas, 1981). While using both editions for practical purposes, some inconsistencies, differences in form, accentuation, localization and in other aspects were detected. Data from interwar questionnaires of Marijampolė County helped to refine the current data as well as supplement the index of Lithuanian rivers and lakes with new hydronyms. Such studies do not only reveal peculiarities of different Lithuanian place names, but also help to find answers to a number of questions related to the evolution of gender and sources of origin of toponyms.
Keywords: onomastika; vandenvardžiai; hidronimai; Marijampolė